Engaging Students in Literature Circles on Critical Reading and Text Analysis - Sutrisno, Djoko (Universitas Muhammadiyah Surakarta, 2018)
To make teaching activities more desirable, different methods and strategies have already been employed constantly. This study utilized the strategy of “literature circles” to improve the text-analysis skills, reading wishes, and interests of potential teachers of Indonesian. “Literature circles” had not been chosen to be utilized as the only real strategy throughout the entire every week class hours; rather, it was used limited to one course hour of each weekly four-hour classes, being complementary to and supportive of other teaching activities. The scholarly study was completed as research. A total of 56 students in two parts of the English department of UMNU Kebumen voluntarily participated in the research. In order to enhance the students’ book reviewing abilities and reading passions, “literature circles” was implemented for a amount of 12 weeks for just one class hour. By the end of the execution of “literature circles” when the students’ reading comprehension post-test and pre-test scores had been compared, a big change was observed. Predicated on the results, it may be figured “literature circles” works well in developing students’ abilities to get the theme, primary idea, and keywords in a text message. Besides, the training students remarked that the implementation of the strategy increased their desire and interest for communication, their self-confidence, cooperative learning, critical thinking, reading without bias objectively, and independent reading skills.